Pre-Reformation London Summoners and the Murder of Richard Hunne - Wunderli, Richard (1982)
The apparitor, usually known by his popular name, the summoner, is a minor character in ecclesiastical administration. Most of what we know about summoners has come from literature, notably from Chaucer's scathing portrait in The Canterbury Tales where the summoner is not given any of the saving graces allowed to other scoundrel-pilgrims. Chaucer's summoner, although an officer of the church courts of moral correction, practised bribery and extortion, and in his illicit sex life ‘was as hot…and lecherous as a sparrow’ his lechery was written on his scabby, syphilitic face. It is not my purpose here to dispel literary illusion, but rather to take a hard look at the world of actual summoners – those with names and careers – in pre-Reformation London. I will then single out one summoner, Charles Joseph, and examine his role in that early sixteenth-century cause célèbre: the affair of Richard Hunne. Joseph, after all, confessed to the murder of Hunne in 1514 and even implicated the vicar-general of London in the crime. With new evidence about summoners, I hope to offer a plausible solution to this baffling case.